Entrepreneurial finance: new frontiers of research and practice: Editorial for the special issue Embracing entrepreneurial funding innovations. Issue 1 (2nd January 2017) - Bellavitis, Cristiano; Filatotchev, Igor; Kamuriwo, Dzidziso Samuel; Vanacker, Tom
Abstract: The proliferation of new sources of entrepreneurial finance potentially makes it easier for ventures to raise capital and grow. To date, entrepreneurial finance literature has developed a rich tradition of research on venture capital and angel finance. However, the emergence of "new" sources of finance, such as crowdfunding and the limited attention paid to "traditional" debt financing and financial bootstrapping, offers opportunities to explore, from different points of view and theoretical perspectives, the challenges that ventures face. The objective of this Special Issue is to explore these new and traditional sources of finance and suggest how these phenomena can extend entrepreneurial finance literature and guide new theory building. This paper outlines the new sources of entrepreneurial finance, and in comparing them with more traditional sources, we propose theoretical and empirical challenges that these new and traditional sources present to entrepreneurship scholars. We also provide a brief summary of papers in the Special Issue and outline promising avenues for future research.